Identifikasi Lapisan Akuifer Menggunakan Resistivity Method 1-dimensi di Dusun Karang Bayan, Parampuan, Kabupaten Lombok Barat - Melinda Dwi Erintina; Aji Syailendra Ubaidillah; Andi Faesal; Agus Kurniawan (Jurnal Ilmiah Giga, 2022)
This study aims to identify aquifer layer at Karang Bayan Village, Parampuan, Lombok Barat District. Aquifer layer is the layer that can store and bring the water because it has high rock porosity. The method used in this study was resistivity method with Schlumberger Configuration. This study used 2 measurement points, namely point 1 and point 2. Each of points has the value of (AB/2) = 300meter. Data were analysed and processed by using software Progress resulting the variation of resistivity value vertically. The result at point 1 shows the aquifer layer is at depth 86.30-128 meters and identified as sandstone with resistivity value 56.50 Ωm. The result at point 2 shows the aquifer layer is at depth 86-128 meter and identified as sandstone with resistivity value 20.28 Ωm.